Optimization of the heat transfer efficiency of a ground source heat pump heating system via FLUENT numerical simulation with fluid–solid coupling - Wei Wei (AIP Advances)
As an energy-saving and environmentally friendly technology, ground source heat pumps (GSHPs) show great potential for use in winter heating and summer cooling. However, existing systems still face the problem of insufficient heat transfer efficiency in practical applications. This study innovatively considers the influence of multiple factors, including circulating water flow, U-tube geometry, and soil thermal conductivity, on the heat transfer efficiency of GSHPs. By using FLUENT software for fluid–solid coupling simulations, we evaluated the system performance under different operating conditions, covering both the winter heating and summer cooling modes. This study revealed that the heat transfer efficiency of the system can be significantly improved by optimizing the circulating water flow, U-tube geometry, and soil thermal conductivity. In particular, the heat transfer efficiency of winter heating increased from 68.3% to 79.1%, while the heat transfer efficiency of summer cooling increased from 72.1% to 80.5%. Sensitivity analysis shows that soil thermal conductivity has the greatest impact on the heat transfer efficiency, followed by the U-tube length, U-tube diameter, and finally, the circulating water flow rate. In conclusion, a comprehensive optimization scheme is proposed, including the use of additive-modified circulating water solution to increase the heat transfer capacity, optimization of the design of U-tubes to improve the heat transfer area, improvement of soil conditions to improve thermal conductivity, and adjustment of the circulating water flow rate to achieve the optimal flow state. This study lays the foundation for the further development of GSHP systems and their wider application.